Predictors of renal and patient outcomes in anti-neutrophil cytoplasmic antibody-associated vasculitis: Our single-center, tertiary care experience - Aysun Toraman; Özgül Soysal Gündüz (Archives of Rheumatology, 2021)
Objectives: This study aims to assess the different predictors of renal and patient prognosis in anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) patients with and without renal involvement. Patients and methods: A total of 79 patients (51 males, 28 females; mean age: 57.3±14.2 years; range, 18 to 71 years) with AAV between January 2006 and November 2019 were retrospectively analyzed. Demographic and laboratory data including the complement 3 (C3) serum levels and renal biopsy findings were extracted from the electronic and printed medical records of the hospital registry. Survival, renal survival, remission, and relapse outcomes were analyzed. Results: A total of 35% of the patients with renal involvement progressed to end-stage renal disease (ESRD). The dialysis requirement at the time of admission (hazard ratio [HR]: 21.95 [2.93-164.22]; p=0.003), estimated glomerular filtration rate (eGFR) (HR: 0.97 [0.94-0.99]; p=0.024) and Five-Factor Score (FFS) ≥2 at the time of diagnosis (HR: 3.59 [1.08-11.94]; p=0.037) were the predictors of ESRD. The five-year patient survival rate was 87.1%. The only predictor of mortality was age (HR: 1.07 [1.01-1.14]; p=0.024). The patients with hypocomplementemia (22%) had a lower remission rate (p=0.049), FFS ≥2 at the time of diagnosis (p=0.026), and higher levels of hematuria (p=0.004) and proteinuria (p=0.037). The FFS ≥2 at the time of diagnosis was an independent predictor of relapse (HR: 8.9 [1.02-77.36]; p=0.047). Conclusion: Our study suggests that the baseline renal function and FFS ≥2 at the time of diagnosis are the major prognostic factors for progression to ESRD in AAV patients. In addition, AAV patients with hypocomplementemia may have a lower remission rate.